Addressing the Limits of Production Resources Through Partnerships to Improve Technical Efficiency: A Case Study of Micro and Small Industries in Indonesia 2014 - Gayatri Waditra Nirwesti; Nachrowi Djalal Nachrowi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2018)
The objective of the study is to understand the correlation between inter-firm cooperation and firm technical efficiency. It based on the background of the difficulties and limited production resources faced by micro and small industry (MSI) that impede them to move toward production frontier that makes the firm less efficient technically. Therefore, this study will discuss whether cooperation conducted by MSI will bring improved technical efficiency. Estimation is taken by using a maximum likelihood method on firm production function stochastically. Using data from Micro and Small Industry Survey Year 2004 published by the National Bureau of Statistic of Indonesia, inter-firm cooperation is measured through an index with Principal Component Analysis which reflects the degree of the cooperation. As the first study in Indonesia for the topic, result shows a positive correlation between inter-firm cooperation and technical efficiency in the micro industry, otherwise, the correlation is not found in small industry. This indicates that inter-firm cooperation is not “panacea” to attain technical efficiency, yet it is depending on the size of the firm.